2005
DOI: 10.1007/s00122-005-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of population size on the estimation of QTL: a test using resistance to barley stripe rust

Abstract: The limited population sizes used in many quantitative trait locus (QTL) detection experiments can lead to underestimation of QTL number, overestimation of QTL effects, and failure to quantify QTL interactions. We used the barley/barley stripe rust pathosystem to evaluate the effect of population size on the estimation of QTL parameters. We generated a large (n = 409) population of doubled haploid lines derived from the cross of two inbred lines, BCD47 and Baronesse. This population was evaluated for barley st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(141 citation statements)
references
References 32 publications
7
132
1
1
Order By: Relevance
“…However, it should be noted that the relatively small size of the mapping population (58 F 2 individuals) has several consequences. In such populations, minor QTL are more difficult to detect and major QTL effects are generally overestimated (Vales et al 2005). Thus the change in the magnitude of QTL effect may, in part, be explained by the elimination of false positives and minor QTLs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the relatively small size of the mapping population (58 F 2 individuals) has several consequences. In such populations, minor QTL are more difficult to detect and major QTL effects are generally overestimated (Vales et al 2005). Thus the change in the magnitude of QTL effect may, in part, be explained by the elimination of false positives and minor QTLs.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the ability to detect QTL -trait associations is limited, because QTL are only detected where there is genetic variation at loci (between the two parental alleles), which has a significant effect on the measured trait. Each line in the mapping population is designed to contribute alleles from either parent, and each line will differ in which parental alleles they contribute at a small number of loci [22]. Therefore, fewer lines results in fewer genetically variable loci.…”
Section: Materials and Methods (A) Quantitative Trait Loci Mapping Popmentioning
confidence: 99%
“…In that way, our experiment is a preliminary study where a certain number of QTLs with small or medium effects might not be detected. Studies showed that by increasing the population size, it is possible to increase the total number of QTLs detected and to reveal those with small effects (Vales et al 2005;Raghavan and Collard 2012). This is well known that the power to detect QTLs is rather low using a small number of individuals, depending on the trait heritability and QTL effects, with also the non-negligible risk to evidence false QTLs especially for those with weak effects (Beavis 1998).…”
Section: Mapping Population and Linkage Mapmentioning
confidence: 99%